Satellite-based Internet a tutorial. - Hu, Yurong (IEEE Communications magazine)
In a satellite-based Internet system, satellites are used to interconnect heterogeneous network segments and to provide ubiquitous direct Internet access to homes and businesses. This article presents satellite-based Internet architectures and discusses multiple access control, routing, satellite transport, and integrating satellite networks into the global Internet